Predicting the performance of mobile ad hoc networks using scaled-down replicas - Papadopoulos, Fragkiskos; Psounis, Konstantinos (My University, 2007)
Experimentation with mobile ad hoc network testbeds is preferred to simulations for performing high fidelity testing. But, at the same time, realistic experimentation with large-scale network testbeds is more difficult, time-consuming, and expensive. To side-step some of these problems several researchers, e.g. [1], [2], have recently suggested experimentation on scaled-down replicas and have managed to downscale some specific indoor network realizations with no mobility. However, the question of whether a scaled-down replica can reproduce the behavior of an arbitrary large-scale mobile ad hoc network, in a timely manner, and under realistic outdoor conditions, remains an interesting open problem. In this work we investigate ways of constructing suitably scaled-down replicas, both in space and time, that can predict the performance of large-scale mobile ad hoc networks with high accuracy. We consider both large- and small-scale fading effects. Further, we present necessary and sufficient conditions for the scaling to be possible, and identify some of the issues that may arise in practice. Finally, we argue that it is not possible to build arbitrarily smaller replicas, and that the factor by which one scales down the original network (in space) depends on the carrier frequency. © 2007 IEEE.